A stochastic particle swarm based model for long term production planning of open pit mines considering the geological uncertainty - Gilani, Seyyed-Omid; Sattarvand, Javad; Hajihassani, Mohsen; Abdullah, Shahrum Shah (Resources policy, 2020)
Long term production planning (LTPP) plays a critical role to achieve success of a mining operation. LTPP, as an optimization problem, aims to maximize the net present value (NPV) of a mine subject to a set of constraints. One of the main reasons for not achieving production targets is the uncertainty of the LTPP's inputs. Geological uncertainty as the main sources of uncertainty is considered in this research. In this regard, a set of equiprobable scenarios of orebody and derived two new block model called “risk block model” and “EType” were used as inputs. Then, a stochastic integer programming (SIP) model was developed to integrate the geological uncertainty. Finally, a PSO-based algorithm was developed to solve the SIP model. Four different strategies were developed, according to the population topology and how to use the risk block model. Population topology defines the subset of particles that effect on each particle. Implementation the proposed approach on a large scale mine demonstrate its performance to develop a unique schedule considering geological uncertainties with maximum NPV and minimum risk of not achieving production targets. Investigations show that Gbest based PSO is more susceptible to trap in local optima. Multiple risk based strategies are able to generate better solutions, however, single risk based strategies are good practices when companies are looking for flexible or specific risk based designs. •A new stochastic optimization algorithm based on PSO is proposed for open pit mine production planning.•Geological uncertainty is considered.•Four different strategies named GPSO-SRB, GPSO-MRB, LPSO-SRB, and LPSO-MRB were developed.•The approach was applied on large scale open pit mine in the northwest of Iran.•Results demonstrate the abilities of approach to create a single schedule that diminishes the risk and also increases the NPV.